2018
DOI: 10.1002/tox.22564
|View full text |Cite
|
Sign up to set email alerts
|

The ethanol extraction of prepared Psoralea corylifolia induces apoptosis and autophagy and alteres genes expression assayed by cDNA microarray in human prostate cancer PC‐3 cells

Abstract: Prostate cancer is the most common male reproductive system cancer. The prevalence of prostate cancer in Europe and the United States is higher than that in the Asian region. However, the treatment of prostate cancer remains unsatisfactory. Psoralea corylifolia has been used to cure this disease as Chinese medicine in the Asian region. In this study, we analyzed the components of ethanol extraction of unprepared and prepared P. corylifolia by HPLC. Psoralen and isopsoralen content from the prepared P. corylifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…The DAVID functional annotation clustering tool was used to detect significantly over‐represented GO biological processes and enrichment was determined at DAVID calculated Benjamini value <0.05. A standard Student's t test was used to measure the significance of overexpression of individual genes . These genes complete with Affymetrix transcript identifiers were uploaded by Microsoft Excel spreadsheet onto Metacore 5.0 software (GeneGo pathways analysis) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DAVID functional annotation clustering tool was used to detect significantly over‐represented GO biological processes and enrichment was determined at DAVID calculated Benjamini value <0.05. A standard Student's t test was used to measure the significance of overexpression of individual genes . These genes complete with Affymetrix transcript identifiers were uploaded by Microsoft Excel spreadsheet onto Metacore 5.0 software (GeneGo pathways analysis) .…”
Section: Methodsmentioning
confidence: 99%
“…A standard Student's t test was used to measure the significance of overexpression of individual genes . These genes complete with Affymetrix transcript identifiers were uploaded by Microsoft Excel spreadsheet onto Metacore 5.0 software (GeneGo pathways analysis) . GeneGo recognizes these genes to the MetaCore data analysis suite for generating maps regarding common pathways or molecular connections between quercetin treated.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported that bavachin has a variety of pharmacological effects, including anti-inflammatory, antioxidation, anti-ageing, anti-bacterial and estrogen-like effects, which molecular structure is shown in Figure 2A. P. corylifolia has been demonstrated to induce autophagy in PC-3 cells (Lin et al, 2018). So, we will further study whether bavachin can activate autophagy in HASMCs.…”
Section: Bavachin Induces Autophagy In Hasmcsmentioning
confidence: 90%
“…Recently, it was shown that osthole (7-metoxy-8-isopenthenocoumarin; 150-250 µM), alone and with TMZ, triggered autophagy in human glioblastoma multiforme (T98G) and anaplastic astrocytoma (MOGGCCM) cells, although the main type of induced death in these cells was apoptosis [197]. Two major coumarins extracted from Psoralea corylifolia (50-400 µg/mL), psoralen and isopsoralen, exerted a cytotoxic effect in prostate cancer cells PC-3, through the induction of apoptosis and autophagy [198]. The induction of autophagic cell death in prostate cancer cells (PC-3 and DU145) was also demonstrated for a geranylated 4-phenylcoumarin (DMDP-1; 9 µM), extracted from the bark of Mesua elegans (Clusiaceae) [199].…”
Section: Coumarinsmentioning
confidence: 99%